Seismic Behavior and Stability Analysis of an Embankment Dam on a Permeable Foundation - Dhiman, Sanchit; Chaturvedy, Gyanendra Kumar; Pandey, Umesh Kumar; Bhandari, Sanjay (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study analyses the behaviour of an embankment type homogenous earth dam with a plastic clay core subjected to an earthquake excitation and its deformation with time. The displacement vs time graph has been plotted under the earthquake excitation and deformation for the structure is found out. The analysis tries to depict the real-life performance of the dam under earthquake excitations for its additional safety consideration. GeoStudio has been used to perform the QUAKE/W analysis on the dam. QUAKE/W models the dynamic stresses arising from earthquake shaking and simulates the impact of these stresses on the earth`s structures. The software is based on the finite element method.
Keywords: QUAKE/W; GeoStudio; Earthquake excitations; SEEP/W; SLOPE/W; Embankment dams